Mompreneurs Potential: An Analysis of Housewives' Entrepreneurial Interest - Alfiana Alfiana; Fajriani Azis; Andi Anggi Kemalasari; Nuraisyiah Nuraisyiah (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine whether there is an interest in entrepreneurship in housewives in Salubarani Village, Gandangbatu Sillanan District, Tana Toraja Regency. The research method used is descriptive qualitative research, how to collect data, namely through observation, interviews, and documentation of the object of research so as to explore more deeply about the analysis of entrepreneurial interest in housewives in Salubarani Village, Gandangbatu Sillanan District, Tana Toraja Regency. As objects in this study are some housewives who have a business or do not have a business. The results obtained from this study stated that most housewives in Salubarani Village, Gandangbatu Sillanan Subdistrict, Tana Toraja Regency do not have an interest in entrepreneurship so that the government needs to play a role in overcoming this problem. Entrepreneurial interest in housewives in Salubarani Village, Gandangbatu Sillanan Subdistrict, Tana Toraja Regency actually has enormous potential for mompreneurs development, but it is not easy because there are internal factors and external factors that become obstacles from housewives themselves to develop themselves into mompreneurs. However, to foster interest in entrepreneurship, the way that can be done is by trying to dig up information from various sources related to the business world that is run, especially in recognizing the potential of mompreneurs.